Dinatonium acetate monohydrate salt

By hydrating unstable denamium acetate (DAA) and recrystallizing, denamium acetate monohydrate (DAM), the problem of DAA instability is solved, and higher physical and chemical stability is achieved, which is suitable for drug preparation.

CN119899125APending Publication Date: 2025-04-29AARDVARK THERAPEUTICS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411879430.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-10-14
Filing Date
2022-10-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing denamium acetate (DAA) is unstable and cannot meet the FDA's regulatory requirements for the stability of active drug ingredients, making it difficult to use as a drug intermediate.

Method used

DAA is hydrated and recrystallized to form stable denamium acetate monohydrate (DAM) to improve its physical and chemical stability.

Benefits of technology

DAM shows better stability under high temperature, stress and humidity conditions, avoiding the degradation of DAA and meeting the stability requirements in drug preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899125A_ABST
    Figure CN119899125A_ABST
Patent Text Reader

Abstract

A novel denatonium acetate monohydrate salt form is disclosed. More particularly, the novel salt forms and crystalline hydrate forms are useful for the treatment and prophylaxis of diseases and disorders such as metabolic syndrome, obesity, NASH, glycemic control / diabetes, and IBD (intestinal disease).
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is a divisional application of an invention application with a filing date of October 13, 2022, a Chinese application number of 202280068811.8, and an invention name of "Denatonium Acetate Monohydrate Salt". This application claims the benefit of priority to U.S. Provisional Application No. 63 / 255,947 filed on October 14, 2021, which is incorporated herein by reference in its entirety for any purpose. Technical Field

[0002] The present disclosure provides a novel denatonium acetate monohydrate salt form. More particularly, the novel salt form and crystalline hydrate form of the present invention can be used to treat and prevent diseases and conditions. In particular, such diseases and conditions include metabolic syndrome, obesity, NASH, glycemic control / diabetes, Prader-Willi syndrome and IBD (intestinal disease). Background Art

[0003] Denatonium acetate is a salt mentioned in US2015 / 0252305 ("The bittering agent is preferably a denatonium salt or a derivative thereof. In one aspect, the bittering agent is a denatonium salt selected from the group consisting of denatonium chloride, denatonium citrate, denatonium sugar, denatonium carbonate, denatonium acetate, denatonium benzoate, and mixtures thereof. In one aspect, the liquid composition comprises a first denatonium salt, and the film comprises a second denatonium salt different from the first denatonium salt."). However, it appears that denatonium acetate has never been synthesized, but is listed as a theoretical salt of many salts with denatonium as a cation. Later, a group of patent applications assigned to Aardvark Therapeutics, Inc. described denatonium acetate as a pharmaceutical composition and included a synthesis method for synthesizing denatonium acetate from lidocaine. See, for example, WO 2021 / 062061. The synthesis method produces anhydrous denatonium acetate (DAA). However, it was subsequently determined that DAA was not stable enough and was not suitable for use as an API (active pharmaceutical ingredient) because DAA did not meet the FDA's regulatory requirements for the stability of active pharmaceutical ingredients. Therefore, there is a need in the art for a more stable salt form of denatonium acetate (DA). Denatonium acetate is known to be useful for treating a variety of conditions, such as metabolic syndrome, obesity, and hyperglycemia. See, for example, WO 2021 / 133908. Summary of the invention

[0004] The present disclosure is based on the discovery that DAA is unstable and degrades under at least some conditions. DAA is hydrated and recrystallized into a stable salt, i.e., denatonium acetate monohydrate (DAM). The present disclosure provides a novel denatonium acetate monohydrate salt and crystalline forms thereof. Denatonium acetate monohydrate salts and crystalline forms can provide advantages in the preparation (such as greater stability), processing and administration of denatonium acetate. In particular, DAM can exhibit improved physical and chemical stability to stress, high temperature and humidity, for example relative to DAA.

[0005] The present disclosure provides a denatonium acetate monohydrate salt of structural formula 1: Preferably, the salt is a crystalline monohydrate. The salt is characterized by being substantially Figure 5A or Figure 5B X-ray powder diffraction (XRPD) spectrum shown.

[0006] The present disclosure further provides a pharmaceutical composition comprising a therapeutically effective amount of a crystalline salt of denatonium acetate monohydrate, the crystalline salt of denatonium acetate monohydrate being combined with one or more pharmaceutically acceptable carriers. The one or more pharmaceutically acceptable carriers may comprise a biocompatible polymer. The biocompatible polymer may be cellulose. The one or more pharmaceutically acceptable carriers may comprise a sugar. The sugar may be a sugar alcohol. The sugar alcohol may be mannitol. The one or more pharmaceutically acceptable carriers may comprise talc. The one or more pharmaceutically acceptable carriers comprise an organic acid. The organic acid may be acetic acid. The pharmaceutical composition may be formulated for oral administration. The pharmaceutical composition may comprise solid particles.

[0007] And the present disclosure provides a method for preparing a crystalline salt of denatonium acetate monohydrate, the method comprising the following steps: contacting a certain equivalent of DAA (anhydrous denatonium acetate) with a lower alkyl isobutyl ketone (such as methyl isobutyl ketone) and water so that the water concentration is greater than 10 weight percent, recovering the resulting solid phase, and removing the solid therefrom. The present disclosure provides a method for preparing the denatonium acetate monohydrate salt described herein, the method comprising contacting anhydrous denatonium acetate with a lower alkyl isobutyl ketone and water to form a solid phase containing denatonium acetate monohydrate. The lower alkyl isobutyl ketone can be methyl isobutyl ketone or ethyl isobutyl ketone. Contacting the anhydrous denatonium acetate with a lower alkyl isobutyl ketone and water forms a composition in which the water concentration is greater than 10 weight percent. The denatonium acetate monohydrate is a crystalline monohydrate. The crystalline monohydrate can be characterized as being substantially as follows Figure 5A or Figure 5B X-ray powder diffraction (XRPD) spectrum shown. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 A synthetic method for making DAM from DAA is shown.

[0009] Figure 2 A formal diagram showing the relationship between the discovered polymorphic patterns of DAM is shown.

[0010] Figure 3 Overlay diffraction patterns of the DAM of pattern 1 (lower trace) and pattern 2 (upper trace) are shown.

[0011] Figure 4 Superimposed diffraction patterns of the DAM of pattern 1 (lower trace) and pattern 5 in red (upper trace) are shown.

[0012] Figure 5A The diffraction pattern of the DAM of pattern 1 is shown.

[0013] Figure 5B A magnified version of a region of the diffraction pattern of the DAM from 0 to approximately 5500 counts is shown. DETAILED DESCRIPTION

[0014] One method for synthesizing DAM starts with lidocaine base, makes denatonium hydroxide, and then prepares DAA. Step 1: Synthesis of denatonium hydroxide from lidocaine

[0015] Add 25 g of lidocaine, 60 ml of water and 17.5 g of benzyl chloride to a reflux apparatus, with stirring and heating at 70°C-90°C. The solution needs to be heated and stirred for 24 h at the values ​​given previously, and the solution needs to be cooled to 30°C. Unreacted reagents are removed with 3×10 mL of toluene. Dissolve 65 g of sodium hydroxide in 65 mL of cold water under stirring, and add it to the aqueous solution under stirring over the course of 3 hours. Filter the mixture, wash with some water, and dry in the open air. Recrystallize in hot chloroform or hot ethanol. Step 2: Preparation of anhydrous denatonium acetate (DAA) from denatonium hydroxide.

[0016] 10 g of denatonium hydroxide (MW: 342.475 g / mol, 0.029 mol), 20 mL of acetone and 2 g of glacial acetic acid (0.033 mol) dissolved in 15 mL of acetone were added to a reflux apparatus, and the mixture was stirred and heated to 35° C. for 3 h. Then evaporated to dryness and recrystallized in hot acetone.

[0017] DAA degrades, and it is found that DAA degrades to (A) lidocaine and benzyl acetate, or it degrades to (B) 2-(diethylamino)-3-phenyl-N-(2,6-dimethylphenylpropionamide. Therefore, DAA requires low temperature to be used as an intermediate. For step 3, DAA is maintained in the organic layer and distilled under vacuum until the temperature reaches 65°C-67°C (<150 Torr). Methyl isobutyl ketone is added and refluxed under vacuum to remove water via azeotropic distillation to form DAM. DAM is crystallized by adding isopropanol. Residual salts are removed. The mixture is distilled under vacuum. Next, methyl isobutyl ketone is added, followed by water. In some embodiments, lower alkyl isobutyl ketone is used instead of methyl isobutyl ketone. In some embodiments, the lower alkyl is C 1-3 Alkyl. In some embodiments, the lower alkyl is methyl or ethyl. The temperature is reduced to <10°C. The remaining solid is separated and washed with methyl isobutyl ketone to produce the final DAM (Denatonium acetate monohydrate).

[0018] The present disclosure provides crystalline denatonium acetate monohydrate. In some embodiments, the crystalline denatonium acetate monohydrate is characterized by being substantially as follows Figure 5A or Figure 5B X-ray powder diffraction (XRPD) spectrum shown.

[0019] In some embodiments, a pharmaceutical composition comprising denatonium acetate monohydrate and a pharmaceutically acceptable carrier is provided. A pharmaceutically acceptable carrier may comprise, for example, a biocompatible polymer (such as cellulose) and / or a sugar (such as, for example, a sugar alcohol (such as mannitol)). In some embodiments, a pharmaceutically acceptable carrier comprises talc. In some embodiments, a pharmaceutically acceptable carrier comprises talc, cellulose and sugar. In some embodiments, the pharmaceutical composition is an oral formulation. In some embodiments, a pharmaceutical composition (e.g., an oral formulation) is a sustained-release cellulose mannitol excipient formulation. In some embodiments, a pharmaceutically acceptable carrier comprises an organic acid (such as acetic acid), which may be present in combination with any of the aforementioned components or a combination of components. The pharmaceutical composition may be formulated for oral administration. The pharmaceutical composition may comprise solid particles. Example 1

[0020] This example describes the characterization of a batch of denatonium acetate monohydrate (DAM) and polymorph screening studies performed with the material. DAM is highly crystalline and its XRPD pattern is designated as pattern 1 ( Figure 5A ; Figure 5B (a magnified version of ).

[0021] Gravimetric vapor sorption (GVS) experiments on DAM and storage under stress conditions showed that the material is very hygroscopic at relative humidity (RH) levels above 80%. Deliquescence was observed after 5 days at 96% RH. It also loses mass when it is at relative humidity levels below 10%. The DAM sample kept at 0% RH converted to pattern 5. This pattern is metastable and converts to pattern 1 within a few hours under ambient laboratory conditions.

[0022] When heated to 150°C (just above the melting point) in DSC, DAM was thermally unstable, with analysis by UPLC showing only about 54.9% of the input material remaining.

[0023] Attempts to prepare amorphous material by freeze drying from a range of solvents, by rapid evaporation or anti-solvent precipitation did not result in amorphous material. The provided pattern 1 was used as input material for polymorph screening studies using 48 solvents as well as solvent / anti-solvent screening studies. During all studies of DAM, 4 additional XRPD patterns were found.

[0024] Pattern 2 was obtained by lyophilizing a solution of DAM in tert-butyl alcohol in an attempt to prepare an amorphous material. After 7 weeks of storage in a closed vial, it was observed to have converted to pattern 1.

[0025] based on 1 By H NMR, pattern 3 (from evaporation of a solution of DAM in ethyl formate) was found to be a mixture of acetate and formate salts of denatonium and therefore not representative of denatonium acetate alone.

[0026] Pattern 4 was obtained from the polymorph screen by evaporation of a solution of DAM in 2-methoxyethanol. Samples reanalyzed by XRPD after 6 weeks storage in sealed vials showed conversion to pattern 1.

[0027] Pattern 5 was obtained by storing the DAM at 0% RH, drying in vacuum at room temperature, or heating to 120°C and flash cooling in the DSC. It was observed to readily convert to pattern 1 after standing on the XRPD pan for 4 hours under ambient laboratory conditions. Figure 2 A formal diagram showing the relationships between the discovered patterns can be seen in .

[0028] A summary of the initial characterization of DAMs is provided in Table 1. Table 1

[0029] The particle size distribution was measured and it was shown that D 90The DAM has a bimodal distribution of about 65 μm. The ES+ mass spectrum of DAM shows an M+ ion of 325.4, which is consistent with a quaternary ammonium component. The sample is highly crystalline. Thermal analysis of DAM carried out at 10°C / min by differential scanning calorimetry (DSC) shows a broad shallow endothermic event between 44°C-124°C, a broad endothermic event starting at 135°C consistent with a possible melting point, and an additional endothermic event between 149°C-206°C. Thermogravimetric analysis (TGA) at 10°C / min shows that the mass loss is 4.3% in 40°C-153°C, 12.3% in 154°C-192°C, and 7.8% in 193°C-220°C, followed by further mass loss.

[0030] Several gravimetric vapor sorption (GVS) experiments were performed to investigate the behavior of DAM over a range of different relative humidity levels. The GVS experiment (GVS1) over a range of relative humidity (40%-90%-0%-90%-0%-40%) showed that DAM was highly hygroscopic, with a 23% mass increase over the 0%-90% relative humidity range (second sorption cycle). Most of the mass increase was observed to occur above 80% RH. It is worth noting that the experiment did not reach equilibrium at the highest humidity stage (even with the approach of allowing up to 24 hours for each stage if equilibrium was not reached), so the 23% mass increase may underestimate the hygroscopicity.

[0031] A GVS experiment (GVS2) was performed using DAM (DAM, batch number: ED21356-001-001-00) to study the behavior of the material at levels up to 80% relative humidity. This experiment used a similar approach to GVS1, but did not involve a step at 90% RH, where large mass changes were observed and equilibrium was not reached. From the start of the adsorption cycle, GVS2 within a relative humidity range (40%-80%-0%-80%-0%-40%) showed a mass increase of 2.1% (within 0%-80% relative humidity in the second adsorption cycle), with most of this mass change (+1.4%) occurring between 0%-10% RH. After the experiment, the material remained a free-flowing powder and XRPD analysis showed a diffraction pattern consistent with Pattern 1.

[0032] A further GVS experiment (GVS 3) was performed with DAM over a range of relative humidity (40%-0%-80%-0%-80%-0%-40%) to investigate whether there was a significant difference in behavior if the sample was not exposed to high (80%) RH before the start of the 0%-80% RH adsorption cycle. This experiment (GVS 3) showed a 2% mass increase from the start of the desorption cycle (both in the first and second adsorption cycles within 0%-80% relative humidity). This was the same for both adsorption cycles in the experiment and is comparable to the result of 2.1% obtained in GVS2. Most of the mass change (increase of 1.3%-1.4%) occurred between 0%-10% RH. After the experiment, the material was still a free-flowing powder and XRPD analysis showed a diffraction pattern consistent with Pattern 1.

[0033] GVS experiments with DAM and storage under stress conditions showed that the material is very hygroscopic at relative humidity levels above 80%. It showed a mass increase of 1.4% between 0%-10% RH, and a mass increase of 2.1% between 0%-80% RH (in GVS2), and a mass increase of 23% between 0%-90% RH (in GVS1). After storage at 96% RH for 5 days, deliquescence was observed. It also loses mass when it is at relative humidity levels below 10%.

[0034] After observing that DAM lost mass when going from 10% RH to 0% RH in the GVS experiment described above, a portion of the DAM was placed in an open vial and kept in the GVS instrument at 0% RH for 2 days. It was then removed from the instrument and a portion was immediately analyzed by XRPD. It showed a diffraction pattern consistent with Pattern 5. Reanalysis of the sample after standing on a pan for 4 hours under ambient laboratory conditions showed a conversion to Pattern 1.

[0035] GVS and storage experiments under stress conditions with DAM showed that the material is very hygroscopic at relative humidity levels above 80%. It also loses mass when placed at relative humidity levels below 10%. The DAM sample kept at 0% RH converted to pattern 5, however this pattern was metastable and converted to pattern 1 within a few hours under ambient laboratory conditions.

[0036] A series of additional DSC experiments were performed to further investigate the thermal behavior of DAM. A DAM sample (5 mg) was heated to 150°C at 10°C / min in the DSC and then cooled to 30°C. After the experiment, the pan was removed from the instrument, opened, and the material (DAM, batch number: ED21356-003-001-00) was investigated to check for signs of degradation. UPLC showed significant signs of degradation, with only about 54.9% of the input material remaining. 1 H NMR also showed evidence of significant degradation.

[0037] A DAM sample (4.55 mg) was heated to 120°C at 10°C / min in the DSC, held at 120°C for 2 minutes, and then cooled to 30°C. After the experiment, the pan was removed from the instrument, opened, and the material investigated to check for signs of degradation. UPLC and 1 H NMR showed no signs of significant degradation.

[0038] DSC experiments with DAM showed that the material was thermally unstable when heated to 150°C, showing significant decomposition by NMR and UPLC. When the sample was briefly heated to 120°C, no significant chemical degradation was observed, but a change in the XRPD diffraction pattern from pattern 1 to pattern 5 was observed. After standing overnight at room temperature, the material returned to pattern 1. Pattern 5 is metastable and converted to pattern 1 under ambient laboratory conditions after standing overnight on the XRPD disk. A summary of the initial and further characterization of DAM is provided in Table 2. Table 2

[0039] A portion of DAM (8 mg) was completely dissolved in tert-butyl alcohol (0.5 mL) and then placed in dry ice to freeze the frozen sample. The frozen sample was lyophilized on a freeze dryer until all solvents were removed. The resulting solid material (DAM, batch number: ED21356-005-001-01) was analyzed by XRPD. It was not amorphous and showed a different pattern from the input. This was designated as pattern 2. Figure 3 The DAM overlay diffraction patterns are shown for Pattern 1 in black and Pattern 2 in red. A sample of Pattern 2 was reanalyzed by XRPD after 7 weeks of storage in a sealed vial and showed a diffraction pattern consistent with Pattern 1.

[0040] A portion of DAM (10.9 mg) was dried in vacuo at room temperature overnight to give solid ED21356-004-001-00. It was analyzed by XRPD and found to be not amorphous. It showed diffraction peaks consistent with crystalline material. It showed a pattern very similar to pattern 1, with an additional peak at 18° 2θ, and some other small differences such as Figure 4 This is designated as pattern 5.

[0041] Under the conditions of these researches, by drying in vacuum, from DCM rapid evaporation, antisolvent precipitation or the attempt of preparing amorphous DAM from water, 1,4-dioxane / water (1: 1), MeCN / water (1: 1) or the tert-butyl alcohol freeze drying does not obtain amorphous material.From DCM rapid evaporation or from water, 1,4-dioxane / water (1: 1) or MeCN / water (1: 1) freeze drying obtains crystalline material consistent with pattern 1.The concentrated solution of DAM in DCM is added to heptane quickly and causes precipitation.By XRPD, the analysis of solid shows the diffraction peak of DAM pattern 1.When from t-BuOH freeze drying, isolate new pattern (designated as pattern 2).After storing 7 weeks in sealed vial, find that it has been converted into pattern 1.

[0042] The DAM sample was dried in vacuum at room temperature to give pattern 5. After storage in a closed vial for 6 weeks, it was found to have converted to pattern 1.

[0043] Attempts were made to crystallize the API (DAM) from a wide range of solvent systems in an attempt to produce new crystalline forms. DAM was used as input material for these screening studies and the solvents selected were primarily ICH Class II and Class III with a range of different properties as shown in Table 3 below. Table 3

[0044] Portions of crystalline DAM (approximately 10 mg each) were treated with solvent until a solution was formed, or until 1 mL was added. The resulting samples were refrigerated (solutions) or shaken at room temperature (suspensions) for several days. After refrigeration, samples that initially formed solutions were checked for signs of solid formation. If solid material had formed, it was analyzed by XRPD. If no solid had formed, the vial was opened and the solution evaporated and the solid residue analyzed by XRPD. For samples that initially formed a suspension - if solids were still present, they were analyzed by XRPD. The supernatant from the suspension was filtered and the filtrate was treated as above for the solution. In some experiments, additional solids were obtained from the evaporation of the filtrate and analyzed by XRPD if the amount of material allowed.

[0045] The results are summarized in Tables 4 and 5 below. Table 4 (Experiments 1-24)

[0046] Most experiments with the first 24 solvents resulted in solid material that gave an XRPD diffraction pattern consistent with Pattern 1. Ethyl formate gave a new pattern (designated Pattern 3), and formic acid gave a syrup after evaporation of the experiment. Further data collected on Pattern 3 indicated that it was a mixture of the formate and acetate salts of denatonium.

[0047] Experiments 25-48 yielded solid materials from nearly all solvents with XRPD diffraction patterns consistent with Pattern 1. Three samples remained in solution even after six weeks of evaporation. A new pattern was obtained from 2-methoxyethanol, which was designated Pattern 4. Table 5 (Experiments 25-48)

[0048] Pattern 2 was obtained by attempting to prepare an amorphous material by freeze-drying a solution of DAM in tert-butanol to obtain DAM (Batch No.: ED21356-005-001-01). Characterization data are summarized in Table 6 below. Table 6 DAM pattern 2

[0049] Pattern 3 was obtained from a polymorph screen by evaporating a solution of DAM in ethyl formate. 1 H NMR analysis showed reduced peaks for acetate and additional peaks for formate. This is consistent with a mixture of formate and acetate salts of denatonium. The characterization data are summarized in Table 7 below. Table 7DAM 7 Pattern 3

[0050] Pattern 4 was obtained from the polymorph screen by evaporation of a solution of DAM in 2-methoxyethanol. Samples reanalyzed by XRPD after 6 weeks of storage in sealed vials showed conversion to Pattern 1. Characterization data are summarized in Table 8 below. Table 8 DAM pattern 4

[0051] Pattern 5 was obtained by storing DAM (Pattern 1) at 0% RH, drying in vacuum at room temperature, or heating to 120°C and flash cooling in a DSC. Pattern 5 converted to Pattern 1 after standing on the XRPD pan for 4 hours under ambient laboratory conditions. It was also found that samples placed on the XRPD pan overnight under ambient laboratory conditions converted to Pattern 1. Samples stored in closed vials for 6 weeks also converted to Pattern 1. A summary of the characterization data for the samples of Pattern 5 can be found in Table 9. Table 9 DAM pattern 5

[0052] DAM is highly crystalline and the XRPD pattern was assigned as Pattern 1. During the study of DAM, 4 additional XRPD patterns were discovered. 1 H NMR, one of them (pattern 3) was found to be a mixture of denatonium acetate and denatonium formate, and therefore not a pattern representing denatonium acetate alone. Pattern 2 was obtained by lyophilizing a solution of DAM in tert-butanol in an attempt to prepare an amorphous material. After storage in a closed vial for 7 weeks, it was observed to have converted to pattern 1. Pattern 4 was obtained from a polymorph screening by evaporating a solution of DAM in 2-methoxyethanol. After storage in a closed vial for 6 weeks, a sample reanalyzed by XRPD showed conversion to pattern 1. Pattern 5 was obtained by storing DAM (pattern 1) at 0% RH, drying in a vacuum at room temperature, or heating to 120°C in a DSC and rapidly cooling. It was observed to be easily converted to pattern 1 after standing on an XRPD disk for 4 hours under ambient laboratory conditions.

Claims

1. A denatonium acetate monohydrate salt of structural formula 1: The denatonium acetate monohydrate salt is a crystalline monohydrate.

2. The salt of claim 1, characterized by an X-ray powder diffraction (XRPD) spectrum substantially as shown in Figure 5A or Figure 5B.

3. A pharmaceutical composition comprising a therapeutically effective amount of a salt according to any one of claims 1 to 2 in combination with one or more pharmaceutically acceptable carriers.

4. The pharmaceutical composition of claim 3, wherein the one or more pharmaceutically acceptable carriers comprise a biocompatible polymer.

5. The pharmaceutical composition of claim 4, wherein the biocompatible polymer is cellulose.

6. The pharmaceutical composition according to any one of claims 3-5, wherein the one or more pharmaceutically acceptable carriers comprises a sugar.

7. The pharmaceutical composition according to claim 6, wherein the sugar is a sugar alcohol.

8. The pharmaceutical composition according to claim 7, wherein the sugar alcohol is mannitol.

9. The pharmaceutical composition according to any one of claims 3-8, wherein the one or more pharmaceutically acceptable carriers comprises talc.

10. The pharmaceutical composition of any one of claims 3-9, wherein the one or more pharmaceutically acceptable carriers comprise an organic acid.

11. The pharmaceutical composition according to claim 10, wherein the organic acid is acetic acid.

12. The pharmaceutical composition according to any one of claims 3-11, wherein the pharmaceutical composition is formulated for oral administration.

13. The pharmaceutical composition according to any one of claims 3 to 12, wherein the pharmaceutical composition comprises solid particles.

14. A method for preparing denatonium acetate monohydrate salt of structural formula 1: The method comprises contacting anhydrous denatonium acetate with an alkyl isobutyl ketone and water to form a solid phase comprising denatonium acetate monohydrate, wherein the alkyl isobutyl ketone is C 1-3 Alkyl isobutyl ketone.

15. The method according to claim 14, comprising the steps of: (1) contacting a certain amount of DAA (anhydrous denatonium acetate) with methyl isobutyl ketone and water so that the water concentration is higher than 10 weight percent, (2) recovering the resulting solid phase, and (3) removing the solid phase therefrom.

16. The method according to claim 14, wherein the alkyl isobutyl ketone is methyl isobutyl ketone or ethyl isobutyl ketone.

17. The method according to any one of claims 14-16, wherein the denatonium acetate monohydrate is a crystalline monohydrate.

18. The method of claim 17, wherein the crystalline monohydrate is characterized by an X-ray powder diffraction (XRPD) spectrum substantially as shown in Figure 5A or Figure 5B.

Citation Information

Patent Citations

  • Compositions comprising a bittering agent

    US20150252305A1

  • Oral pharmaceutical immediate release composition and method of treatment for weight loss

    WO2021062061A1

  • Pharmaceutical composition for treatment or prevention of multiple inflammatory disorders

    WO2021133908A1